Temporal and spatial expression of terpene synthase genes associated with agarwood formation in Aquilaria malaccensis Lam - Anor Basah, Azzarina; Mohamed, Rozi; Shiou, Yih Lee; Salleh @ Japri, Mohd Nazre (SpringerOpen, 2016)
Background The diseased wood, agarwood, from the tropical tree taxa Aquilaria, is famed for its unique fragrance and medicinal values, mainly due to its richness in secondary metabolites such as the sesquiterpenes. The presence of sesquiterpenes in high numbers and amounts correlates with agarwood of high quality.